A description of the clinical signs and lesions of African swine fever, and its differential diagnoses in pigs slaughtered at selected abattoirs in central Uganda - Ekakoro, John E.; Nassali, Aisha; Hauser, Cole; Ochoa, Krista; Ndoboli, Dickson; Okwasiimire, Rodney; Kayaga, Edrine B.; Wampande, Eddie M.; Havas, Karyn A. (Frontiers in Veterinary Science, 2025)
IntroductionAfrican swine fever (ASF) is a contagious and hemorrhagic viral disease of pigs that may present as a per-acute, sub-acute or chronic disease. Prior to this study, the clinical and pathologic presentation of ASF in pigs slaughtered in Uganda had not been characterized, and studies varied in their findings regarding differential diagnoses. The objectives of this study were to: (1) describe the clinical and pathologic presentation of ASF in pigs sampled from abattoirs in the Kampala metropolitan area over the course of one year, and (2) determine the prevalence of swine influenza A viruses (S-IAV), porcine reproductive and respiratory syndrome virus (PRRSV), classical swine fever virus (CSFV), and Salmonella spp. in these pigs.MethodsClinical and pathological data and samples were collected from pig abattoirs located in the Kampala metropolitan area from May 2021 through June 2022. Confirmatory diagnostic testing for African swine fever virus (ASFV) was performed using the real-time PCR (qPCR) assay. Diagnostic testing for ASFV differential diagnoses were performed using serologic and molecular techniques.ResultsSevere fever was found in 3.3% (26/794) of all pigs that were ASFV positive by any of the sample types tested. Of 196 blood positive pigs, 26% (51) had widespread splenic hemorrhages compared to 15.2% (67/442) of the pigs positive based on testing of lymph nodes, 15.5% (72/464) of pigs positive based on tonsil samples, and 15.8% (61/385) of pigs with positive spleen samples. The median gross pathologic lesion score for all pigs that tested positive for any sample type was six out of 33 [interquartile range (IQR): 4, 9]. Overall, 89.3% of the pig samples (1,188/1,330) were seropositive for S-IAV, and 0.8% (11/1,329) were seropositive for PRRSV. As for Salmonella spp., 4.4% (40/903) were qPCR positive, and all samples tested for CSFV nucleic acid were negative.ConclusionASF in pigs slaughtered in central Uganda presents with clinical signs and lesions that vary; they present as healthy pigs or pigs with subacute or acute disease. However, surveillance programs in Uganda will require confirmatory laboratory diagnosis due to the occurrence of pathogens that cause similar clinical signs and lesions.